(untitled) (Research, Society and Development, 2022)
Within the pandemic context, there was an increase in people’s experience in the virtual world, especially children and adolescents. So, arises the need to identify signs of misuse of this tool, as well as of its consequences in the public in question. In this sense, this work seeks to analyze the scientific literature on the impact of cyberbullying on the mental health of children and adolescents during the COVID-19 pandemic. As for the methodology, an integrative literature review was carried out based on the analysis of articles published between 2020 and 2022, available in the databases: Pubmed, BVS, Scielo and Lilacs. The guiding question of the article was: what was the impact of cyberbullying on the mental health of children and adolescents during the COVID-19 pandemic? The results found were the significant increase in the incidence of cyberbullying among children and adolescents during the COVID-19 pandemic, triggering relevant consequences in this population, with symptoms of anxiety, depression and suicidal ideation being the main consequences of this practice. In conclusion, it was found that there was a significant impact of cyberbullying on the mental health of children and adolescents during the COVID-19 pandemic. At last, the creation of an application that allows interactions between victims and a preventive school program are amongst the most effective interventions.